The Influence of Loading Path on Fault Reactivation: A Laboratory Perspective. Issue 8 (23rd April 2021) - Giorgetti, C.; Violay, M.
Abstract: The loading path the fault experiences is often neglected when evaluating its potential for reactivation and the related seismic risk. However, stress history affects fault zone compaction and dilation, and thus its mechanics. Therefore, in incohesive fault cores that could dilate or compact, the role of the loading path could not be ruled out. Here we reproduce in the laboratory different tectonic loading paths for reverse (load‐strengthening in the absence of significant fluid pressure increase) and normal gouge‐bearing faults (load‐weakening) to investigate the loading path influence on fault reactivation and seismic potential. We find that, before reactivation, experimental reverse faults undergo compaction, whereas experimental normal faults experience dilation . Additionally, when reactivated at comparable normal stress, normal faults are more prone to slip seismically than reverse faults. We infer that the higher mean stress normal faults experience compacts more efficiently the fault rock, increasing its stiffness and favoring seismic slip. Plain Language Summary: Slip along pre‐existing faults in the Earth's crust occurs whenever the shear stress resolved on the fault plane overcomes its frictional strength, potentially generating catastrophic earthquakes. The increase in the shear stress can follow different tectonic loading paths, and in particular, load‐weakening versus. load‐strengthening paths when it is coupled respectively to a decrease versus. an increase in the normal stress clamping the fault. The role of the loading path cannot be ruled out, especially in the presence of a thick, incohesive fault zone that can change its volume under different stress conditions. However, in most friction experiments, the fault is loaded under constant or increasing the normal stress, that is, load‐strengthening. Here, we bridge the gap in laboratory loading paths simulating reactivation at the same normal stress clamping the fault but with different tectonic stress histories. Interestingly, our results suggest contrasting hydro‐mechanical behavior for load‐strengthening versus. load‐weakening path: (1) before reactivation, fault zone compaction versus. dilation and (2) when reactivated at comparable normal stress, stable creep versus seismic slip, respectively. Our study has only scratched the surface of the loading‐path influence on thick fault stability and potential implications for fluid circulation in fault zones, stressing the importance of further investigating the loading path influence. Key Points: Before slip, gouge in reverse faults (load‐strengthening path) compacts, whereas gouge in normal faults (load‐weakening path) dilates The mean stress that the fault experiences before reactivation affects its compaction state, and thus its stiffness The stress path history of a fault influences its seismic behavior, especially in the presence of thick gouge‐bearing fault zones